A health risk assessment and early alcohol intervention program for non-mandated students. Issue 5 (22nd June 2022) - Welter, Trisha L.; Rossmann, Patrick D.; Hines, Haley E.
Abstract: Objective: We examined the effects of a two-part intervention including an online health risk assessment with personalized feedback and a brief in-person alcohol intervention for high-risk students. Participants: Participants were 1, 987 sophomore students, with 259 completing the alcohol intervention and 91 completing all follow-up surveys. Methods: Students were invited to take an initial online health assessment covering a range of health behaviors and subsequent 3-month follow-up survey. Students who reported high-risk alcohol behaviors on the assessment were invited to participate in two one-on-one sessions utilizing motivational interviewing. Follow-up surveys occurred 3, 6 and 12 months later. Results: Students who completed the health risk assessment reported knowledge and behavior changes. Students who completed the in-person alcohol intervention showed significant reductions in alcohol risk behavior 3-, 6- and 12-months post-intervention. Conclusions: A two-part intervention for non-mandated students including a health risk assessment and one-on-one intervention shows promise in reducing alcohol risk.